SCROLL TECHNIQUE LEARNING IN MAKING OF CREATIVE WOOD PRODUCTS IN STUDENT CLASS XI KRIYA KAYU SMK NEGERI 9 SURAKARTA YEAR OF 2017/2018 - Taufan Amirullah Abiyoga; , Edy Tri Sulistyo; Nanang Yulianto (Proceeding of International Conference on Art, Language, and Culture, 2017)
Scroll Technique Learning in Making Of Creative Wood Products  in  Student Class XI Kriya Kayu SMK Negeri 9 Surakarta Year of 2017/2018. The purpose of this stuudy was to determine : (1) the learning implementation of scroll technique in making of creative wood products in student class XI Kriya Kayu SMK Negeri 9 Surakarta. (2) the extent of students interest in receiving the learning of scroll technique in making of creative wood products in student class XI Kriya Kayu SMK Negeri 9 Surakarta. (3) visualization of creative wood products produced by student. This study used a qualitative approach. The data was selected are informant, places, events, and archival documents. Techniques used in data collection were observation, interviews, documentation, and questionaires. The sampling techniques used purposive sampling. The validity test of the data used the triangulation of data, and review the informant. The analysis of the data used interactive analysis model were: data collection, data reduction, data presentation, and conclusions. The results of this study indicated that: (1) teacher prepared the lesson plans, then the learning was performed for five meetings. The teacher applies contextual teaching and learning model with scientific approach. The learning methods used include lecture, question and answer, demonstration, experimentation, skill / drill methods, and assignment. . Learning media used in the form of power point slides, learning video tutorials, examples of products produced by scroll techniques, and teaching aids. Learning evaluation by assessing aspects of affective, cognitive, and psychomotor. The process of making the work consists of several steps, among others  the preparation of materials, making design, pasting design, cutting process, assembly process, and finishing. (2) students interest in learning scroll technique is categorized as very interested, it is shown from high score, student enthusiasm, and student discipline in following learning. (3) overall visualization of the resulting product is good, mastery of the technique is good enough, and neat. The resulting product design has applied the principles of art that is unity, balance, proportion, and contrast. The development of design exploration has been good, but the resulting product has not met the criteria as a creative product.